1989
DOI: 10.1128/jb.171.10.5452-5457.1989
|View full text |Cite
|
Sign up to set email alerts
|

The translation start signal region of TEM beta-lactamase mRNA is responsible for heat shock-induced repression of amp gene expression in Escherichia coli

Abstract: pBR322 contains the amp gene encoding ,-lactamase. When Escherichia coli carrying this plasmid is exposed to heat shock, ,B-lactamase synthesis is repressed transiently at the translational level. To identify the DNA element responsible for this translational repression, DNA segments containing the translation start region of the amp gene were excised from pAT153 and fused in frame with the lacZ reading frame in the open reading frame vector pORF1. These constructs were introduced into E. coli, and the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, they also concluded that this regulation was independent of the rpoH allele (26). Kuriki showed that the heat shock-induced suppression of ,-lactamase synthesis was regulated by the initiation of translation and depended on a short nucleotide sequence containing the Shine-Dalgarno sequence and the ATG start codon of ,-lactamase (16,17).In contrast, there is evidence from yeast cells that mRNA degradation can affect the suppression of the synthesis of non-heat shock proteins during the heat shock response. A temperature shift from 23 to 36°C resulted in a decrease in the synthesis of ribosomal proteins, with a corresponding rapid decrease in the cellular levels of ribosomal protein mRNAs (14).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, they also concluded that this regulation was independent of the rpoH allele (26). Kuriki showed that the heat shock-induced suppression of ,-lactamase synthesis was regulated by the initiation of translation and depended on a short nucleotide sequence containing the Shine-Dalgarno sequence and the ATG start codon of ,-lactamase (16,17).In contrast, there is evidence from yeast cells that mRNA degradation can affect the suppression of the synthesis of non-heat shock proteins during the heat shock response. A temperature shift from 23 to 36°C resulted in a decrease in the synthesis of ribosomal proteins, with a corresponding rapid decrease in the cellular levels of ribosomal protein mRNAs (14).…”
mentioning
confidence: 95%
“…However, they also concluded that this regulation was independent of the rpoH allele (26). Kuriki showed that the heat shock-induced suppression of ,-lactamase synthesis was regulated by the initiation of translation and depended on a short nucleotide sequence containing the Shine-Dalgarno sequence and the ATG start codon of ,-lactamase (16,17).…”
mentioning
confidence: 99%
“…The most preferred sequence of strong RBS in E . coli is believed to be [ 23 ]. To enhance the expression of the α-subunit and NhlE, the putative RBS ( ) between the nhlB and nhlA genes ( Fig 1A ) was replaced with an enhanced RBS ( ), and the spacing sequences between the two genes were shortened from 63 bp to 14 bp, constructing plasmid pET24a- nhlBrbsAE .…”
Section: Resultsmentioning
confidence: 99%
“…Both promoters and the intervening regions downstream of the start codons show no significant similarity to those of the TEM /?-lactamases (Russell & Bennett,198 l), to inducible promoters of chromosomally encoded /?-lactamases (Lindberg & Normark, 1986;Forsman et af., 1989) or to regulatory sequences sensitive to heatIabile protein, which may couple the /?-lactamase expression to the SOS response (Kuriki, 1989).…”
Section: Discussionmentioning
confidence: 99%